2013
DOI: 10.1016/j.ajpath.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 Targets Lymphatic Vessels in the Eye and Draining Lymph Node of Mice Leading to Edema in the Absence of a Functional Type I Interferon Response

Abstract: Herpes simplex virus type-1 (HSV-1) induces new lymphatic vessel growth (lymphangiogenesis) in the cornea via expression of vascular endothelial growth factor by virally infected epithelial cells. Here, we extend this observation to demonstrate the selective targeting of corneal lymphatics by HSV-1 in the absence of functional type I interferon (IFN) pathway. Specifically, we examined the impact of HSV-1 replication on angiogenesis using type I IFN receptor deficient (CD118(-/-)) mice. HSV-1-induced lymphatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Infectious or traumatic insults involving the cornea can compromise its immunoprivileged status and consequently permit substantial pathological sequelae, including leukocyte infiltration, corneal edema, hypoesthesia (sensation loss), and neovascularization. Following HSV-1 infection in mice, pathological corneal edema and neovascularization ensue commensurate with epithelial thinning within geographic corneal lesions (1,2,44). Similar to corneal neovascularization, hypoesthesia is a hallmark of herpes stromal keratitis in mice and humans and results from denervation of the epitheliumassociated subbasal mechanosensory nerve fibers (40,45,46).…”
Section: Resultsmentioning
confidence: 99%
“…Infectious or traumatic insults involving the cornea can compromise its immunoprivileged status and consequently permit substantial pathological sequelae, including leukocyte infiltration, corneal edema, hypoesthesia (sensation loss), and neovascularization. Following HSV-1 infection in mice, pathological corneal edema and neovascularization ensue commensurate with epithelial thinning within geographic corneal lesions (1,2,44). Similar to corneal neovascularization, hypoesthesia is a hallmark of herpes stromal keratitis in mice and humans and results from denervation of the epitheliumassociated subbasal mechanosensory nerve fibers (40,45,46).…”
Section: Resultsmentioning
confidence: 99%
“…5A). We have previously shown that HSV-1 McKrae gains access to the draining lymph nodes and disrupts adaptive immune responses in CD118 Ϫ/Ϫ mice (62,66,67); however, this is not observed with HSV-1 0ΔNLS or KOS-GFP (Fig. 4).…”
Section: Discussionmentioning
confidence: 85%
“…6C). Virulent HSV-1 strains such as McKrae have been shown to infect every layer of the cornea in CD118 Ϫ/Ϫ mice and destroy lymphatic vessels during acute infection (29,67). The acute death of these animals pursuant to HSV-1 infection has rendered investigating late pathology in the eye impossible until now.…”
Section: Discussionmentioning
confidence: 99%
“…Anpt2 is reportedly generated by macrophages and lymphatic endothelial cells in the cornea [22]. It is tempting to speculate the loss of Angpt2 levels may be due to the depletion of macrophages and/or lymphatic endothelium of which the latter is specifically targeted in the presence of high viral content [23] and the former has been found in the anterior stroma of human corneas [24]. At no time was IL-17 detected which suggests that the influx of inflammatory cells including neutrophils [25] are a likely source of this pro-inflammatory cytokine in response to HSV-1 infection.…”
Section: Discussionmentioning
confidence: 99%